Esophagitis and Gastritis Recent Updates - Neri, Vincenzo; Ahmed, Monjur (IntechOpen, 2021)
This book provides a comprehensive overview of esophagitis and gastritis and the many manifestations of these conditions. Chapters cover such topics as gastroduodenal ulcers, infectious pathologies of the esophagus, gastrointestinal pathophysiological testing for upper GI disorders, and more.